The Importance of Gamma Aminobutyric Acid Produced by Lactic Acid Bacteria - Seda Yalçınkaya; Gülden Başyiğit Kılıç; Aynur Gül Karahan Çakmakçı (Turkish Journal of Agriculture: Food Science and Technology)
Gamma aminobutyric acid (GABA) is known as an important inhibitory neurotransmitter in the human brain. Recent studies have proved the beneficial effects of GABA on human health. It has been reported that in people who use GABA supplements, the factors affecting the life quality negatively such as psychological problems, insomnia and immune problems have decreased. Studies in this field have shown that lactic acid bacteria (LAB) can produce GABA. For this reason, interest in LAB producing GABA is steadily increasing. It is stated that GABA produced by natural LAB has almost no side effects compared to synthetically created ones. It is also suggested that GABA-producing LAB, which is isolated from especially in Far East countries foods, should be used to develop functional foods. More research needs to be done in order to proceed in this newly developing area, and the undiscovered features of GABA need to be investigated. In this review, the importance of GABA is addressed and the studies about GABA are examined.